Gig Workers and Policies of Minimal Social Dislocation. Issue 2 (3rd April 2021) - Spithoven, Antoon
Abstract: My analysis of the process of digital "platformization" of economies is framed in Thorstein Veblen's theory of economic evolution and John R. Commons' concept of reasonableness. I conclude that digital platformization of economies is rooted in a deliberately decided liberalization of markets. The consequences of liberalization require a fundamental revision of economic policy and socio-economic institutions if one wants to create permanent jobs with good social security provisions, and/or to establish reasonable income/wealth differentials.